Geestelijke verzorging als casus van de ontkerkelijking - Schilderman, Hans (Religie & Samenleving, 2013)
This contribution offers an exploration of spiritual care as a professional discipline that profiled itself during the eighties of last century in the Netherlands as a typical provision that deals with vital questions, issues of meaning and existential problems of patients and clients from the perspective of their religion or philosophy of life. In settings of defence, justice and healthcare, provisions for spiritual care are increasingly confronted with the consequences of declining church attendance and secularization, which this contribution aims to clarify by analysing some problems of legitimation, professionalization and public policymaking. The double bind in spiritual care which requires commitments to the requirements of church and care illustrates an ongoing struggle to offer the best care possible while dealing with the opportunities and threats emerging from the rapidly changing landscapes of both religion and care in Dutch society. A final paragraph offers some suggestions for repertoire development in spiritual care.